The Impact of Influencer Marketing on Brand Awareness, Customer Brand Engagement, and Overall Brand Quality: Evidence from Optimum Gym Yogyakarta - Aziz Ikko Wanaden Mantofani; Alldila Nadhira Ayu Setyaning (Indonesian Journal of Business Analytics, 2026)
The objective of this study is to investigate the impact of influencer marketing on brand awareness, customer brand engagement, and overall brand quality in the fitness industry, particularly at Optimum Gym Yogyakarta. The increase in competition in the fitness industry as well as the shift toward digital marketing strategies using influencers, as applied by Optimum Gym using the fitness influencer "Om Yudis", motivate this study. Following the screening procedure, which yielded 229 replies, the data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4.0. 142 of these answers were deemed legitimate. The findings demonstrate that customer brand engagement, brand awareness, and overall brand quality are all positively and significantly impacted by influencer marketing. Overall brand quality, however, is not much impacted by brand awareness. On the other hand, Influencer Marketing and Overall Brand Quality are mediated by Customer Brand Engagement, which has a major influence on Overall Brand Quality. These results imply that improving consumer engagement is more crucial to the success of influencer marketing tactics than merely raising brand recognition. In order to improve the image of brand quality, Optimum Gym is advised to concentrate on tactics that promote customer engagement and involvement.